Enhancement of flexural strength of glass fiber reinforced polymer laminates using multiwall carbon nanotubes. (5th November 2018) - Singh, K. K.; Chaudhary, S. K.; Venugopal, R.
Abstract : In this work, advance/multiscale nanocomposite were made by adding different amount (0, 0.5, 1.25, and 2 wt%) of multiwall carbon nanotubes (MWCNTs) to glass fiber reinforced polymer (GFRP) composites by hand lay‐up and vacuum bagging technique. Flexural strength and interlaminar shear strength (ILSS) of composites were performed on unfilled and MWCNTs‐filled glass fiber/epoxy nanocomposite to identify the effect of adding nanotubes on the mechanical properties. For understanding the structure and morphology of advance nanocomposite, the dispersion states were studied using field emission scanning electron microscopy (FE‐SEM). Mechanics of fracture behavior in different test were also discussed in details. POLYM. ENG. SCI., 59:E248–E261, 2019. © 2018 Society of Plastics Engineers